Unusual Case of Utero-Ovarian Prolapse Concurrent with Cystocele in a Queen - Seyedhosein Jarolmasjed (Iranian Journal of Veterinary Surgery, 2017)
Case Description- A 1-year-old female Domestic Shorthair cat weighing 2.5 kg with one week history of protruding mass from the vulva was admitted. Clinical Findings- The prolapse was complete involving both horns protruding from the vulva and a soft bulging mass was palpable inside the prolapsed uterus. Treatment and Outcome- The prolapsed organ was irrigated with warm saline solution and the debris was cleaned. A ventral midline celiotomy was performed for reduction of the mass and sterilization of the cat. The urinary bladder was incarcerated in the right horn of the uterus. The left ovary was inside the mass beside the bladder. Ovarian pedicles were intact but broad ligament was torn. An ovariohysterectomy was performed. Clinical Relevance- Complete uterine prolapse is an emergency case of surgery. If the prolapse includes abdominal contents, amputation of the mass may be avoided and reduction of the uterus and abdominal contents through celiotomy should be prioritized. It seems that this case is the first report of an ovarian prolapse coincident with retroversion of the uterus. The prognosis following ovariohysterectomy is excellent if shock and hemorrhage are treated appropriately.